Lithium-rich manganese-based composite positive electrode material and preparation method and application thereof
By using the coordinated cooperation of high-entropy oxide materials Mg, Zn, Cu and Nb on the surface of lithium-rich manganese-based positive electrode material, the problem of poor voltage attenuation and rate performance of the material during circulation is solved, and structural stability and performance improvement is achieved .
Patent Information
- Application Number
- CN202411347855.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Lithium-rich manganese-based positive electrode materials have problems with poor voltage attenuation and rate performance during circulation, which is mainly due to the structural instability caused by transition metal migration and oxygen loss, which affects its application potential.
The coordinated cooperation of high-entropy oxide materials Mg, Zn, Cu and Nb is adopted to enhance the stability of the core through the surface structure, inhibit transition metal migration and oxygen loss, and improve electron conductivity, thereby improving the material's cycling and rate performance.
The circulation and rate performance of lithium-rich manganese-based composite cathode material is significantly improved, structural stability is enhanced, transition metal dissolution and oxygen loss are avoided, and the overall performance of the battery is improved.
Smart Images

Figure CN119230780A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a lithium-rich manganese-based composite positive electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electric vehicles and energy storage facilities, the market demand for high energy density lithium-ion batteries is increasing. Layered lithium-rich manganese-based oxides (LLOs for short) are a new type of lithium battery cathode material that can undergo reversible redox reactions of anions and cations. They have a much higher discharge capacity than traditional lithium cobalt oxide cathode materials and high nickel ternary cathode materials, so they have great potential in the development of high energy density lithium batteries.
[0003] The energy density of lithium-ion batteries depends on the specific capacity and redox potential of their electrode materials. Compared with traditional layered positive electrode materials, the actual discharge specific capacity of lithium-rich manganese-based positive electrode materials has reached more than 300mAh / g, and the discharge average voltage is about 3.5V. It is currently the most competitive and potential positive electrode material for power lithium-ion batteries. Although lithium-rich manganese-based positive electrode materials have the above advantages, there are also many problems: the coulomb efficiency corresponding to the first charge and discharge process is low, the interface between the electrode and the electrolyte is unstable, the lithium ion diffusion coefficient is low, the rate performance is not ideal, and the voltage decay and energy density decrease during the cycle.
[0004] Among them, since part of the transition metal in the lithium-rich manganese-based cathode material is transferred to the tetrahedral gap during the cycle, the material structure will change to spinel, resulting in voltage decay; and since the lithium-rich manganese-based cathode material produces chemically inactive Mn4 + , resulting in a decrease in the conductivity of the material; in addition, the poor kinetic performance of the material itself also leads to poor rate performance. Therefore, voltage decay and poor rate performance are two very critical factors that hinder the practical application of lithium-rich manganese-based positive electrode materials.
[0005] The common method to improve the cycle performance of lithium-rich manganese-based cathode materials is to coat the surface of lithium-rich manganese-based cathode materials with electrochemically inert substances (such as Al2O3) or to use electrochemically inert elements (such as Al 3+ , Ti 4+ , Zr 4+) The surface of the lithium-rich manganese-based positive electrode material is doped. These two methods can effectively improve the structural stability of the surface layer of the lithium-rich manganese-based positive electrode material. However, the above methods often cause a significant decrease in the initial capacity and rate performance of the lithium-rich manganese-based positive electrode material. Therefore, the amount of coating or doping elements introduced is usually very small, but this will affect the improvement of the material's cycle performance, such as the zirconium phosphate (inner layer) / calcium fluoride (outer layer) double-coated lithium-rich material disclosed in CN106058203A. In addition, the literature (Adv. Mater. 2013, 25, 3722-3726) has reported the use of spinel lithium manganese oxide (belonging to the Fd-3m space group) coated lithium-rich manganese-based positive electrode materials. Since spinel lithium manganese oxide itself has electrochemical activity, the first efficiency and initial capacity of the coated lithium-rich manganese-based positive electrode materials are significantly improved. However, the lithium-rich manganese-based positive electrode materials usually need to be discharged to 2V when used, which has exceeded the discharge cut-off voltage when spinel lithium manganese oxide is used alone. At this voltage, the Mn ions in the spinel coating layer will undergo the Jan-Taylor effect, which will cause the coating layer to crack and aggravate the problem of Mn ion dissolution. Therefore, although the single coating of spinel lithium manganese oxide can suppress the problem of oxygen precipitation on the surface of the lithium-rich manganese-based positive electrode material, the improvement in the material's cycle performance is limited.
[0006] Therefore, how to improve the rate performance and cycle performance of lithium-rich manganese-based positive electrode materials is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lithium-rich manganese-based composite positive electrode material and its preparation method and application. The positive electrode material provided by the present invention inhibits the migration of transition metals in the positive electrode material and the loss of oxygen through the synergistic coordination of Mg, Zn, Cu and Nb in the surface high entropy oxide material, and the electronic conductivity is also improved, thereby greatly improving the cycle performance and rate performance of the lithium-rich manganese-based composite positive electrode material.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a lithium-rich manganese-based composite positive electrode material, which comprises a lithium-rich manganese-based matrix material core and a high-entropy oxide material coated on the surface of the core; the metal elements in the high-entropy material include Mg, Zn, Cu and Nb.
[0010] It should be noted that the high entropy oxide material in the present invention is a mixed oxide material in which the components of Mg, Zn, Cu and Nb are evenly distributed, that is, an oxide material of a combination of multiple metal elements.
[0011] The lithium-rich manganese-based composite positive electrode material provided by the present invention has a synergistic combination of surface high entropy structures Mg, Zn, Cu and Nb, which enhances the overlap between the O2p state and the transition metal-oxygen occupied state, and further improves the surface structure stability. Mg can inhibit the migration of transition metal ions and avoid the dissolution of transition metal elements. Zn and Nb can form strong covalent bonds with oxygen in the inner core, thereby inhibiting the loss of oxygen. Cu can effectively improve the electronic conductivity, thereby greatly improving the cycle performance and rate performance of the lithium-rich manganese-based composite positive electrode material under the action of the high entropy oxide material.
[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] Preferably, the inner core of the lithium-rich manganese-based matrix material includes a lithium-rich manganese-based core and a lithium-rich manganese-based core layer from the inside to the outside.
[0014] Preferably, the lithium-rich manganese-based core has a general chemical formula of (1-x)LiMn a M 1-a O2·xLi2MnO3, the general chemical formula of the lithium-rich manganese-based core layer is (1-x)LiMn b N 1-b O2·xLi2MnO3, wherein 0<x≤0.4, 0.5≤a≤0.8, a>b, and the M and the N each independently include a non-manganese transition metal element.
[0015] For example, x can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 or 0.4, and a can be 0.5, 0.53, 0.55, 0.58, 0.6, 0.63, 0.65, 0.68, 0.7, 0.73, 0.75, 0.78 or 0.8, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In the present invention, the core of the lithium-rich manganese-based matrix material may include other transition metal elements in addition to manganese, including but not limited to Ni and the like.
[0017] In the present invention, the inner core of the lithium-rich manganese-based matrix material can achieve simultaneous improvement of capacity and cycle performance by setting a core-shell structure with high manganese in the core and relatively lower manganese content in the core layer; the inner core adopts the synergistic cooperation of the core-shell structure and the surface high entropy to significantly improve the cycle stability and rate performance, and the core-shell structure can improve the structural stability while ensuring high specific capacity; the synergistic cooperation of the surface high entropy structure Mg, Zn, Cu and Nb enhances the overlap between the O2p state and the transition metal-oxygen occupied state, further improving the surface structural stability, wherein Mg can inhibit the migration of transition metal ions and avoid the dissolution of transition metal elements, Zn and Nb can form strong covalent bonds with oxygen in the inner core, thereby inhibiting the loss of oxygen, and Cu can effectively improve the electronic conductivity, thereby greatly improving the cycle performance and rate performance of the lithium-rich manganese-based composite positive electrode material under the action of the high entropy oxide material.
[0018] Preferably, in the high entropy oxide material, taking the total molar amount of Mg, Zn, Cu and Nb as 100%, the molar proportions of Mg, Zn, Cu and Nb are kept consistent.
[0019] In the high entropy oxide material provided by the present invention, the molar ratios of Mg, Zn, Cu and Nb remain consistent, which can better realize the formation of a high entropy structure, thereby being more conducive to improving rate performance and cycle stability.
[0020] Preferably, taking the total atomic weight of all elements in the lithium-rich manganese-based composite positive electrode material as 100%, the atomic percentage of the total atomic weight of Mg, Zn, Cu and Nb in the high entropy oxide material is 0.2at% to 3.0at%, for example, 0.2at%, 0.5at%, 1at%, 1.5at%, 2at%, 2.5at% or 3at%, etc.
[0021] In a second aspect, the present invention provides a method for preparing the lithium-rich manganese-based composite positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0022] The core of the lithium-rich manganese-based precursor matrix material is first mixed with a lithium source, and then first sintered to obtain an intermediate material;
[0023] The intermediate material, Mg salt, Zn salt, Cu salt and Nb salt are mixed for a second time and sintered for a second time to obtain the lithium-rich manganese-based composite positive electrode material.
[0024] Preferably, the D50 of the inner core of the lithium-rich manganese-based precursor matrix material is 7 to 16 μm, for example, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm.
[0025] Preferably, the inner core of the lithium-rich manganese-based precursor matrix material includes a lithium-rich manganese-based precursor core and a lithium-rich manganese-based precursor core layer from the inside to the outside.
[0026] Preferably, the chemical formula of the lithium-rich manganese-based precursor core is Mn a M 1-a (OH)2, the general chemical formula of the core layer of the lithium-rich manganese-based precursor is Mn b N 1-b (OH)2, wherein 0.5≤a≤0.8, a>b, and the M and the N each independently include a non-manganese transition metal element.
[0027] Preferably, the D50 of the lithium-rich manganese-based precursor core is 2 to 12 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm.
[0028] Preferably, the method for preparing the lithium-rich manganese-based precursor core comprises:
[0029] Adding a first mixed salt solution, a first precipitant solution and a first complexing agent solution in parallel to perform a first coprecipitation reaction to obtain a lithium-rich manganese-based precursor core;
[0030] After obtaining the lithium-rich manganese-based precursor core, the second mixed salt solution, the second precipitant solution and the second complexing agent solution are added in parallel to perform a second coprecipitation reaction to obtain the lithium-rich manganese-based precursor matrix material core.
[0031] It should be noted that the specific preparation process of the coprecipitation reaction of the precursor core of the lithium-rich manganese-based precursor matrix material provided by the present invention is a conventional technical solution. Except for the above limitations, the remaining preparation raw materials, preparation parameters, etc. can be adaptively selected and adjusted according to actual needs by those skilled in the art;
[0032] Specifically, the concentrations of the first mixed salt solution and the second mixed salt solution are independently 1.6 to 2.4 mol / L, such as 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.8 mol / L, 2 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L or 2.4 mol / L, etc., and the types of mixed salts include but are not limited to at least one of nickel-manganese-based sulfate, nickel-manganese-based nitrate or nickel-manganese-based chloride, etc.;
[0033] The concentrations of the first precipitant solution and the second precipitant solution are independently 9 to 12 mol / L, such as 9 mol / L, 10 mol / L, 11 mol / L or 12 mol / L, etc., and the first precipitant and the second precipitant independently include but are not limited to sodium hydroxide and / or potassium hydroxide, etc.;
[0034] The concentrations of the first complexing agent solution and the second complexing agent solution are independently 8 to 10 mol / L, such as 8 mol / L, 9 mol / L or 10 mol / L, etc., and the first complexing agent and the second complexing agent independently include ammonia water and / or citric acid, etc.;
[0035] The reaction temperature of the first coprecipitation reaction and the second coprecipitation reaction is independently 30 to 80°C, for example, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C;
[0036] The pH values of the first coprecipitation reaction and the second coprecipitation reaction are each independently 9 to 13, for example, 9, 9.3, 9.5, 9.8, 10, 10.3, 10.5, 10.8, 11, 11.3, 11.5, 11.8, 12, 12.3, 12.5, 12.8 or 13;
[0037] Furthermore, after the second coprecipitation reaction is completed, the material is aged, washed and dried in sequence to obtain a lithium-rich manganese-based precursor matrix material core;
[0038] Those skilled in the art can make adaptive selections and adjustments based on the above preparation process according to the specific defined target of the precursor core of the lithium-rich manganese-based precursor matrix material.
[0039] Preferably, the first sintering temperature is 800-1000°C, such as 800°C, 850°C, 900°C, 950°C or 1000°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0040] Preferably, the first sintering time is 5 to 20 hours, for example 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In the first sintering process provided by the present invention, the specific material type selection of the lithium source and the amount of lithium source added are both conventional technical solutions. For example, the lithium source includes but is not limited to at least one of lithium hydroxide, lithium carbonate, lithium acetate or lithium nitrate, and the ratio of the total molar amount of lithium in the lithium source to the core of all metal elements in the manganese-based matrix material precursor is (1-2):1 and does not include the endpoint values of 1 and 2.
[0042] Preferably, the second mixing comprises liquid phase mixing.
[0043] Preferably, the liquid phase mixing comprises liquid phase mixing using ethanol as a solvent.
[0044] In the present invention, the specific preparation process of the liquid phase mixing includes: mixing the intermediate material, Mg salt, Zn salt, Cu salt and Nb salt with ethanol as solvent, continuously stirring for 5 to 15 hours (for example, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, etc.), drying, and then performing a second sintering.
[0045] Preferably, the second sintering temperature is 500-700°C, such as 500°C, 550°C, 600°C, 650°C or 700°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0046] Preferably, the second sintering time is 4 to 8 hours, such as 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0047] As a preferred technical solution, the preparation method comprises the following steps:
[0048] Adding a first mixed salt solution, a first precipitant solution and a first complexing agent solution in parallel to perform a first coprecipitation reaction to obtain a lithium-rich manganese-based precursor core;
[0049] After obtaining the lithium-rich manganese-based precursor core, adding the second mixed salt solution, the second precipitant solution and the second complexing agent solution in parallel to perform a second coprecipitation reaction to obtain the lithium-rich manganese-based precursor matrix material core;
[0050] The inner core of the lithium-rich manganese-based precursor matrix material includes a lithium-rich manganese-based precursor core and a lithium-rich manganese-based precursor core layer from the inside to the outside. The chemical formula of the lithium-rich manganese-based precursor core is Mn a M 1-a (OH)2, the general chemical formula of the core layer of the lithium-rich manganese-based precursor is Mn b N 1-b (OH)2, wherein 0.5≤a≤0.8, a>b, and the M and the N each independently include a non-manganese transition metal element;
[0051] The precursor core of the lithium-rich manganese-based precursor matrix material is first mixed with a lithium source, and first sintered at 800 to 1000° C. for 5 to 20 hours to obtain an intermediate material;
[0052] The intermediate material, Mg salt, Zn salt, Cu salt and Nb salt are mixed in liquid phase under ethanol solvent, and the mixture is second sintered at 500-700° C. for 4-8 hours to obtain the lithium-rich manganese-based composite positive electrode material.
[0053] In a third aspect, the present invention further provides a lithium-ion battery, comprising the lithium-rich manganese-based composite positive electrode material as described in the first aspect or the lithium-rich manganese-based composite positive electrode material prepared by the preparation method as described in the second aspect.
[0054] It should be noted that due to space limitations and to avoid redundancy, the present invention does not list all point values within the above numerical range one by one, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] The lithium-rich manganese-based composite positive electrode material provided by the present invention has a synergistic combination of surface high entropy structures Mg, Zn, Cu and Nb, which enhances the overlap between the O2p state and the transition metal-oxygen occupied state, and further improves the surface structure stability. Mg can inhibit the migration of transition metal ions and avoid the dissolution of transition metal elements. Zn and Nb can form strong covalent bonds with oxygen in the inner core, thereby inhibiting the loss of oxygen. Cu can effectively improve the electronic conductivity, thereby greatly improving the cycle performance and rate performance of the lithium-rich manganese-based composite positive electrode material under the action of the high entropy oxide material. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is an SEM image of the core of the manganese-based matrix material precursor provided in Example 1.
[0058] Figure 2 This is a SEM image of the lithium-rich manganese-based composite positive electrode material provided in Example 1. DETAILED DESCRIPTION
[0059] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0061] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0062] Example 1
[0063] This embodiment provides a lithium-rich manganese-based composite positive electrode material, the lithium-rich manganese-based composite positive electrode material comprising a lithium-rich manganese-based matrix material core and a high-entropy oxide material coated on the surface of the core; the metal elements in the high-entropy material include Mg, Zn, Cu and Nb;
[0064] The inner core of the lithium-rich manganese-based matrix material includes a lithium-rich manganese-based core (LiMn 0.75 Ni 0.25 O2·0.1Li2MnO3 and lithium-rich manganese-based core layer (LiMn 0.6 Ni 0.4 O2·0.1Li2MnO3);
[0065] Taking the total atomic weight of all elements in the lithium-rich manganese-based composite positive electrode material as 100%, the atomic percentage of the total atomic weight of Mg, Zn, Cu and Nb in the high entropy oxide material is 1 at %.
[0066] The preparation method of the lithium-rich manganese-based composite positive electrode material is as follows:
[0067] (1) preparing a sulfate solution A and a solution B containing nickel ions and manganese ions with a total ion concentration of 2 mol / L, wherein the molar ratio of nickel ions to manganese ions in solution A is 25:75, and the molar ratio of nickel ions to manganese ions in solution B is 40:60;
[0068] Industrial liquid alkali with a concentration of 10 mol / L was used as the precipitant solution C, and ammonia water with a concentration of 8 mol / L was used as the complexing agent solution D;
[0069] A base liquid E containing a precipitant solution and a complexing agent solution (ammonia water) is prepared in a reactor, the pH of E is controlled at 12, the concentration of ammonia water in E is 2-4 g / L, and nitrogen is introduced as an inert protective gas, and a mixed salt solution A, a precipitant solution C and a complexing agent solution D are added to the reactor in parallel to perform a first coprecipitation reaction. During the first coprecipitation reaction, the pH is controlled at 9-9.5, the stirring speed is 300-600 rpm, and the reaction temperature is 55° C., to obtain a lithium-rich manganese-based precursor core with a target particle size D50 of 11 μm;
[0070] Solution A is replaced with solution B, and the second coprecipitation reaction is continued to obtain a lithium-rich manganese-based precursor with a target particle size D50 grown to 12 μm, wherein the inner core of the lithium-rich manganese-based precursor matrix material includes a lithium-rich manganese-based precursor core and a lithium-rich manganese-based precursor core layer from the inside to the outside;
[0071] The obtained spherical lithium-rich manganese-based precursor matrix material precursor core is aged, centrifuged, washed, dried, and magnetic foreign matter is removed to obtain a precursor material;
[0072] (2) mixing lithium hydroxide and the precursor prepared in step (1) in a high-speed mixer at a molar ratio of 1.2:1, and then performing a first sintering at 800° C. for 8 h in an air atmosphere to obtain a lithium-rich manganese-based matrix positive electrode material (intermediate material);
[0073] (3) The obtained intermediate material, MgCl2, Zn(CH3COO)2·2H2O, C2H5ONb, and CuCl2 (the molar ratio of Mg, Zn, Nb, and Cu is 1:1:1:1) are added to an ethanol solution, and after continuous stirring for 8 hours, the solution is dried at 100°C, and then annealed (second sintering) at 600°C for 6 hours to obtain the lithium-rich manganese-based composite positive electrode material.
[0074] Figure 1 The SEM image of the core of the manganese-based matrix material precursor provided in Example 1 is shown.
[0075] Figure 2 The SEM image of the lithium-rich manganese-based composite positive electrode material provided in Example 1 is shown.
[0076] Example 2
[0077] This embodiment provides a lithium-rich manganese-based composite positive electrode material, the lithium-rich manganese-based composite positive electrode material comprising a lithium-rich manganese-based matrix material core and a high-entropy oxide material coated on the surface of the core; the metal elements in the high-entropy material include Mg, Zn, Cu and Nb;
[0078] The inner core of the lithium-rich manganese-based matrix material includes a lithium-rich manganese-based core (LiMn 0.6 Ni 0.4 O2·0.05Li2MnO3 and lithium-rich manganese-based core layer (LiMn 0.5 Ni 0.5 O2·0.05Li2MnO3);
[0079] Taking the total atomic weight of all elements in the lithium-rich manganese-based composite positive electrode material as 100%, the atomic percentage of the total atomic weight of Mg, Zn, Cu and Nb in the high entropy oxide material is 0.5 at %.
[0080] The preparation method of the lithium-rich manganese-based composite positive electrode material is as follows:
[0081] (1) preparing a sulfate solution A and a solution B containing nickel ions and manganese ions and having a total ion concentration of 2 mol / L, wherein the molar ratio of nickel ions to manganese ions in solution A is 40:60, and the molar ratio of nickel ions to manganese ions in solution B is 50:50;
[0082] Industrial liquid alkali with a concentration of 10 mol / L was used as the precipitant solution C, and ammonia water with a concentration of 1 mol / L was used as the complexing agent solution D;
[0083] A base liquid E containing a precipitant solution and a complexing agent solution (ammonia water) is prepared in a reactor, the pH of E is controlled at 12.3, the concentration of ammonia water in E is 2-4 g / L, and nitrogen is introduced as an inert protective gas, and a mixed salt solution A, a precipitant solution C and a complexing agent solution D are added to the reactor in parallel to perform a first coprecipitation reaction. During the first coprecipitation reaction, the pH is controlled at 9-9.5, the stirring speed is 300 rpm, and the reaction temperature is 45° C., to obtain a lithium-rich manganese-based precursor core with a target particle size D50 of 10 μm;
[0084] Solution A is replaced with solution B, and the second coprecipitation reaction is continued to obtain a lithium-rich manganese-based precursor matrix material core with a target particle size D50 grown to 14 μm, wherein the lithium-rich manganese-based precursor matrix material core includes a lithium-rich manganese-based precursor core and a lithium-rich manganese-based precursor core layer from the inside to the outside;
[0085] The obtained spherical lithium-rich manganese-based precursor matrix material precursor core is aged, centrifuged, washed, dried, and magnetic foreign matter is removed to obtain a precursor material;
[0086] (2) mixing lithium hydroxide and the precursor prepared in step (1) in a high-speed mixer at a molar ratio of 1.4:1, and then performing a first sintering at 1000° C. for 10 h in an air atmosphere to obtain a lithium-rich manganese-based matrix material core (intermediate material);
[0087] (3) The obtained intermediate material, MgCl2, Zn(CH3COO)2·2H2O, C2H5ONb, and CuCl2 (the molar ratio of Mg, Zn, Nb, and Cu is 1:1:1:1) are added to an ethanol solution, and after continuous stirring for 8 hours, the solution is dried at 100°C, and then annealed (second sintering) at 700°C for 4 hours to obtain the lithium-rich manganese-based composite positive electrode material.
[0088] Example 3
[0089] The difference between this embodiment and embodiment 1 is that the core of the lithium-rich manganese-based matrix material in this embodiment is a non-core-shell structure, that is, the chemical formula of the core of the lithium-rich manganese-based matrix material is LiMn 0.75 Ni 0.25 O2·0.1Li2MnO3;
[0090] In the preparation method, solution B is not prepared, and solution A is directly used as the preparation raw material to carry out a coprecipitation reaction until a lithium-rich manganese-based precursor matrix material core with a target particle size D50 grown to 12 μm is obtained.
[0091] The rest of the preparation methods and parameters were the same as those in Example 1.
[0092] Example 4
[0093] The difference between this embodiment and embodiment 1 is that in the high entropy oxide material of this embodiment, the molar ratio of magnesium, zinc, niobium and copper is 2:2:3:3.
[0094] The rest of the preparation methods and parameters were the same as those in Example 1.
[0095] Example 5
[0096] The difference between this embodiment and embodiment 1 is that the mixing method in step (3) of this embodiment is solid phase mixing, that is, the intermediate material, MgCl2, Zn(CH3COO)2·2H2O, C2H5ONb, CuCl2 (the molar ratio of Mg, Zn, Nb and Cu is 1:1:1:1) are ball-milled and mixed in a ball mill.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Comparative Example 1
[0099] The difference between this comparative example and Example 1 is that the lithium-rich manganese-based composite positive electrode material of this comparative example does not contain a high entropy oxide material on the surface;
[0100] In the preparation method, step (3) is not performed.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Comparative Example 2
[0103] The difference between this comparative example and Example 1 is that the high entropy oxide material of this comparative example does not contain Mg, and the molar ratio of Zn, Cu and Nb is readjusted to 1:1:1;
[0104] In the preparation method, anhydrous magnesium chloride is not added in step (3).
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Comparative Example 3
[0107] The difference between this comparative example and Example 1 is that the high entropy oxide material of this comparative example does not contain Cu, and the molar ratio of Zn, Mg and Nb is readjusted to 1:1:1;
[0108] In the preparation method, copper chloride is not added in step (3).
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 1 is that the high entropy oxide material of this comparative example does not contain Zn, and the molar ratio of Cu, Mg and Nb is readjusted to 1:1:1;
[0112] In the preparation method, zinc acetate is not added in step (3).
[0113] The rest of the preparation methods and parameters were the same as those in Example 1.
[0114] The lithium-rich manganese-based composite positive electrode material, acetylene black and PVDF provided in Examples 1-5 and Comparative Examples 1-4 were mixed uniformly in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone, stirred uniformly and coated on aluminum foil to prepare a positive electrode sheet;
[0115] The positive electrode sheet, polypropylene separator (Celgrad2400), lithium sheet and electrolyte (1 mol / L LiPF6 dissolved in EC:DEC:EMC (mixed solvent) with a volume ratio of 1:1:1) were assembled in a glove box filled with high-purity argon to obtain a CR2032 button-type lithium-ion battery.
[0116] The battery performance tests provided by Examples 1-5 and Comparative Examples 1-4 were conducted under the following test conditions: a charge-discharge cycle test was conducted at a charge-discharge rate of 1C within a voltage range of 2.1 to 4.6 V. The test results are shown in Table 1.
[0117] Table 1
[0118] 1C capacity (mAh / g) Capacity retention rate (400 cycles) Example 1 275.2 85.6% Example 2 275.7 83.8% Example 3 284.3 73.4% Example 4 274.5 83.7% Example 5 268.6 68.7% Comparative Example 1 277.1 66.4% Comparative Example 2 275.3 80.4% Comparative Example 3 275.4 79.2% Comparative Example 4 274.6 81.1%
[0119] In summary, the lithium-rich manganese-based composite positive electrode material provided by the present invention, the synergistic coordination of the surface high entropy structure Mg, Zn, Cu and Nb enhances the overlap between the O2p state and the transition metal-oxygen occupied state, further improving the surface structure stability, wherein Mg can inhibit the migration of transition metal ions and avoid the dissolution of transition metal elements, Zn and Nb can form strong covalent bonds with the oxygen in the inner core, thereby inhibiting the loss of oxygen, and Cu can effectively improve the electronic conductivity, thereby greatly improving the cycle performance and rate performance of the lithium-rich manganese-based composite positive electrode material under the action of the high entropy oxide material.
[0120] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium-rich manganese-based composite positive electrode material, characterized in that: The lithium-rich manganese-based composite positive electrode material comprises a lithium-rich manganese-based matrix material core and a high-entropy oxide material coated on the surface of the core; the metal elements in the high-entropy material include Mg, Zn, Cu and Nb.
2. The lithium-rich manganese-based composite positive electrode material according to claim 1, characterized in that: The inner core of the lithium-rich manganese-based matrix material includes a lithium-rich manganese-based core and a lithium-rich manganese-based core layer from the inside to the outside; Preferably, the lithium-rich manganese-based core has a general chemical formula of (1-x)LiMn a M 1-a O2·xLi2MnO3, the general chemical formula of the lithium-rich manganese-based core layer is (1-x)LiMn b N 1-b O2·xLi2MnO3, wherein 0<x≤0.4, 0.5≤a≤0.8, a>b, and the M and the N each independently include a non-manganese transition metal element.
3. The lithium-rich manganese-based composite positive electrode material according to claim 1 or 2, characterized in that: In the high entropy oxide material, the total molar amount of Mg, Zn, Cu and Nb is 100%, and the molar amount ratios of Mg, Zn, Cu and Nb are kept consistent; Preferably, based on the total atomic weight of all elements in the lithium-rich manganese-based composite positive electrode material being 100%, the atomic percentage of the total atomic weight of Mg, Zn, Cu and Nb in the high entropy oxide material is 0.2 at% to 3.0 at%.
4. A method for preparing a lithium-rich manganese-based composite positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The core of the lithium-rich manganese-based precursor matrix material is first mixed with a lithium source, and then first sintered to obtain an intermediate material; The intermediate material, Mg salt, Zn salt, Cu salt and Nb salt are mixed for a second time and sintered for a second time to obtain the lithium-rich manganese-based composite positive electrode material.
5. The preparation method according to claim 4, characterized in that: The D50 of the core of the lithium-rich manganese-based precursor matrix material is 7 to 16 μm; Preferably, the inner core of the lithium-rich manganese-based precursor matrix material includes a lithium-rich manganese-based precursor core and a lithium-rich manganese-based precursor core layer from the inside to the outside; Preferably, the chemical formula of the lithium-rich manganese-based precursor core is Mn a M 1-a (OH)2, the general chemical formula of the core layer of the lithium-rich manganese-based precursor is Mn b N 1-b (OH)2, wherein 0.5≤a≤0.8, a>b, and the M and the N each independently include a non-manganese transition metal element; Preferably, the D50 of the lithium-rich manganese-based precursor core is 2 to 12 μm.
6. The preparation method according to claim 5, characterized in that: The method for preparing the lithium-rich manganese-based precursor core comprises: Adding a first mixed salt solution, a first precipitant solution and a first complexing agent solution in parallel to perform a first coprecipitation reaction to obtain a lithium-rich manganese-based precursor core; After obtaining the lithium-rich manganese-based precursor core, the second mixed salt solution, the second precipitant solution and the second complexing agent solution are added in parallel to perform a second coprecipitation reaction to obtain the lithium-rich manganese-based precursor matrix material core.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The temperature of the first sintering is 800-1000° C., and the time of the first sintering is 5-20 hours.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The second mixing includes liquid phase mixing; Preferably, the liquid phase mixing comprises liquid phase mixing using ethanol as a solvent; Preferably, the temperature of the second sintering is 500-700° C., and the time of the second sintering is 4-8 hours.
9. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: Adding a first mixed salt solution, a first precipitant solution and a first complexing agent solution in parallel to perform a first coprecipitation reaction to obtain a lithium-rich manganese-based precursor core; After obtaining the lithium-rich manganese-based precursor core, adding the second mixed salt solution, the second precipitant solution and the second complexing agent solution in parallel to perform a second coprecipitation reaction to obtain the lithium-rich manganese-based precursor matrix material core; The inner core of the lithium-rich manganese-based precursor matrix material includes a lithium-rich manganese-based precursor core and a lithium-rich manganese-based precursor core layer from the inside to the outside. The chemical formula of the lithium-rich manganese-based precursor core is Mn a M 1-a (OH)2, the general chemical formula of the core layer of the lithium-rich manganese-based precursor is Mn b N 1-b (OH)2, wherein 0.5≤a≤0.8, a>b, and the M and the N each independently include a non-manganese transition metal element; The precursor core of the lithium-rich manganese-based precursor matrix material is first mixed with a lithium source, and first sintered at 800 to 1000° C. for 5 to 20 hours to obtain an intermediate material; The intermediate material, Mg salt, Zn salt, Cu salt and Nb salt are mixed in liquid phase under ethanol solvent, and the mixture is second sintered at 500-700° C. for 4-8 hours to obtain the lithium-rich manganese-based composite positive electrode material.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-rich manganese-based composite positive electrode material as described in any one of claims 1 to 3 or the lithium-rich manganese-based composite positive electrode material prepared by the preparation method as described in any one of claims 4 to 9.
Citation Information
Patent Citations
High-entropy ceramic modified positive electrode material and preparation method and application thereof
CN115050940A
Non-heterogeneous layered positive electrode material with high-configuration-entropy surface layer
CN116706007A
Lithium-rich manganese-based material as well as preparation method and application thereof
CN116706018A
Disordered defect state core-shell high-entropy lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN118335928A
